From original equipment manufacturers to total solution providers: emergence of a global manufacturing virtual network in the electronics industry. (1st January 2003) - Shi, Yongjiang; Gregory, Mike
A large scale of vertical disintegration or outsourcing in electronics companies has been transforming the manufacturing industry from a product-based business towards a new generation of network mainly collaborating with customer-solution integrators and specialised manufacturing service providers. This paper seeks to gain a better understanding of the practical background and theoretical issues behind the emerging phenomenon. Based on preliminary case studies in the transformation, the paper proposes a conceptualisation for the Global Manufacturing Virtual Network (GMVN) and compares it with other alternative manufacturing systems. It suggests that GMVN has many distinguished characteristics and therefore can be one of the most hopeful manufacturing configurations based on the cyber space and collaborative infrastructure for the future in which dramatic changes and market individualisation become a part of normal life.